PEMANFAATAN LIMBAH SERBUK BESI SEBAGAI AGREGAT HALUS PADA CAMPURAN ASPAL PANAS - Bahri, Samsul (Inersia: Jurnal Teknik Sipil, 2017)
One of innovation in research is utilizing an industrial waste to obtain value-added. The purpose of this study is to find the effect of and Marshall characteristic value comparison between normal asphalt hotmix and the one which fine aggregate is replaced with waste iron filings. The study was conducted in the laboratory to test Marshall method. The composition of fine aggregate replacement with waste iron powder set at 0%, 25%, 50%, 75%, and 100%. The result showed that variation which met the specifications of the optimum bitumen content and parameter were only variation of 0% and a variation of 25%. Variation at 25% is superior in terms of the fulfillment of the Marshall parameters. When the fine aggregate replaced with iron filings waste by 25%, the use of bitumen was more efficient at 17.86%. Therefore, waste iron powder can be used as a substitute for the refined agegrat A mixture of asphalt with a maximum level of 25%.